(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the graphical forms of poetic texts and their cognitive-pragmatic features in meaning conveyance, drawing on classifications by global linguists. The study examines topographemics, supragraphemics, and syngraphemics in the context of poetic texts. These approaches emphasize the role of visual-graphic representation, such as punctuation, font variations, and graphical layouts, in enriching the semantic and emotional depth of poetry. Analyzing examples from modern Uzbek poetry, the research demonstrates how these elements foster a cognitive-pragmatic interaction between the author and the reader, enhancing interpretative engagement and aesthetic appreciation.